The new gold rush: the new multinationals and the commodification of public sector work. (1st October 2008) - Ursula Huws,
Abstract : This article describes the growth of the new 'public services industry' and outlines the way in which government-provided services can be transformed into commodities and opened up as new fields of activity for private companies. Pointing out that many of these companies have become major transnational enterprises, it then goes on to introduce the other articles in this collection, which focus on the commodification, corporatisation and privatisation of a range of public and government support services, including health, education, transport, energy and water supply, telecommunications, waste disposal, customer services, IT support and postal services. Many of these articles focus on the impact of restructuring on industrial relations, labour processes, working conditions and occupational identities and conclude that these developments are associated with the intensification and casualisation of work, derecognition of unions and continuing elaborations of the international division of labour.